Analisis Kendala dan Solusi dalam Penerbitan SP2D di BPKD Padang Pariaman - Fani Izwar; Syamsir Syamsir; Nia Aprilian; Rafi Putra Kurniawan; S. Amanda Putri; Syakira Mishwa Hanifah (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
The Regional Financial Management Agency (BPKD) of Padang Pariaman Regency is tasked with managing the Padang Pariaman regional finances. One of the archives managed is the Fund Disbursement Order (SP2D). SP2D archives must be maintained properly because in some cases they can be used as authentic evidence. Problems often arise when managing and searching SP2D archives because there are no records of where the archives are stored. Therefore, a system is needed that can support this process. This system was built using the Laravel and Vue.JS frameworks. Laravel has various features that make the system development process easier, and Vue.Js is used because it allows the page display to be more responsive. This system uses QR codes to store SP2D archive location information. System development begins with data collection, system and database design using data flow diagrams (DFDs) and entity-relationship diagrams (ERDs), as well as implementing these diagrams into the system. The result of this development is a system that supports the process of managing and retrieving SP2D archives at BPKD Padang Pariaman Regency. Analysis of obstacles and solutions in issuing SP2D, to obtain information regarding the system and procedures for issuing Fund Disbursement Orders (SP2D) to Regional Financial Agencies, or Regional Financial Management Officials (PPKD), as Proxy of Regional General Treasurer (BUD). This SP2D is a letter used to disburse funds through the designated bank after the Payment Order is received by the BUD Attorney. The procedure starts from RKA-SKPD, DPA-SKPD, KAS-SKPD BUDGET, SPD, SPP, SPM and then SP2D is issued.